Anthropological study on Chagas Disease: Sociocultural construction of illness and embodiment of health barriers in Bolivian migrants in Rome, Italy - Castaldo, Miriam (PLoS One, 2020)
INTRODUCTION: Chagas Disease (CD) is endemic in many Latin-American countries, Bolivia in particular. It is now spreading in Italy as a host country for transcontinental migrants and becoming an emerging health problem. This anthropological action–research, as part of a wider medical project on Neglected Tropical Diseases, has the purpose of analyzing the sociocultural construction of CD and its representation in Bolivian people living in Rome as well as barriers, such as the stigma about the illness, to access the National Health Service for those potentially affected. METHODS: The ethnographic study was carried out from 2016 to 2018 by a medical anthropologist at the National Institute for Health, Migration and Poverty (INMP) on 72 Bolivian migrants (47 women and 25 men) living in Rome. The study was carried out through: a territorial mapping of Bolivian networks and communities aimed at recruiting people, participant observation, and application of semi-structured and unstructured interviews. The interviews were hold in Spanish and proposed to all participants before or during medical examination, or during events organized by the Bolivian community in Rome. The interview consisted of 16 items and covered four macro areas: personal and migration history, health status, access to the Italian National Health Service and knowledge about CD; plus 5 items for those who received a diagnosis of Chagas Disease in Italy. RESULTS: The sociocultural construction and the deep stigma about the illness built by participants and their families could hinder both diagnosis and treatment. Institutional barriers also contributed to reduce adherence to screening tests: often, opening hours of the outpatient clinic were incompatible with participants’ precarious employments. To guarantee participant’s access to public health services and their adherence to the diagnostic protocol, we implemented a profound revision of our cultural and institutional approach to them. CONCLUSIONS: The analysis evidenced the limitations of the conventional approach applied by the Italian National Health Service to this migrant community, such as the absence of socio-cultural and linguistics competences that can help understanding patients’ perception and representation of the illness. The multidisciplinary approach instead—with clinicians using the ethnographic results to adjust their work to the participants’ needs—was a successful attempt to ensure therapeutic alliance.